2021
DOI: 10.1093/trstmh/traa197
|View full text |Cite
|
Sign up to set email alerts
|

A study of 87 mycetoma patients seen at three health facilities in Nouakchott, Mauritania

Abstract: Background Mycetoma is a chronic, progressive and destructive inflammatory disease that affects the skin, subcutaneous and other tissues. The objective of this study was to identify all cases of mycetoma diagnosed in three health facilities in Nouakchott, Mauritania during 2016–2018. Methods This retrospective hospital-based study was conducted at the Dermatology, Orthopedics, Mycology and Pathology departments of the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Gender parity in agriculture sector is appreciable and young male workers are the main work force. In this study we observed that gender predilection was higher for male in both eumycetoma and actinomycetoma group; this finding is similar to published data from this region and other parts of the world [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Gender parity in agriculture sector is appreciable and young male workers are the main work force. In this study we observed that gender predilection was higher for male in both eumycetoma and actinomycetoma group; this finding is similar to published data from this region and other parts of the world [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is endemic in tropical and subtropical regions; however, researchers all over the globe have reported its presence [29][30][31]. It prevails in what is known as the "mycetoma belt," stretching between the latitudes 15˚South and 30N orth; however, this is not inclusive as it was reported from 102 countries worldwide [32,33]. The geographical distribution of the individual causative microorganisms is variable [34].…”
Section: Mycetoma Geographical Spatial Distributionmentioning
confidence: 99%
“…Mycetoma presents in two forms according to the causative agent; eumycetoma caused by fungal agents and actinomycetoma caused by a group of filamentous bacteria [ 6 9 ]. Young adult males are mostly affected by this condition, although all age groups and gender are susceptible [ 10 , 11 ]. Affected communities are usually underprivileged with poor access to education and safe sanitation [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%